How Should Social Media Be Used in Transplantation? A Survey of the American Society of Transplant Surgeons. Issue 3 (March 2019) - Henderson, Macey L.; Adler, Joel T.; Van Pilsum Rasmussen, Sarah E.; Thomas, Alvin G.; Herron, Patrick D.; Waldram, Madeleine M.; Ruck, Jessica M.; Purnell, Tanjala S.; DiBrito, Sandra R.; Holscher, Courtenay M.; Haugen, Christine E.; Alimi, Yewande; et al.
Abstract : Background: Social media platforms are increasingly used in surgery and have shown promise as effective tools to promote deceased donation and expand living donor transplantation. There is a growing need to understand how social media-driven communication is perceived by providers in the field of transplantation. Methods: We surveyed 299 members of the American Society of Transplant Surgeons about their use of, attitudes toward, and perceptions of social media and analyzed relationships between responses and participant characteristics. Results: Respondents used social media to communicate with: family and friends (76%), surgeons (59%), transplant professionals (57%), transplant recipients (21%), living donors (16%), and waitlisted candidates (15%). Most respondents (83%) reported using social media for at least 1 purpose. Although most (61%) supported sharing information with transplant recipients via social media, 42% believed it should not be used to facilitate living donor-recipient matching. Younger age ( P = 0.02) and fewer years of experience in the field of transplantation ( P = 0.03) were associated with stronger belief that social media can be influential in living organ donation. Respondents at transplant centers with higher reported use of social media had more favorable views about sharing information with transplant recipients ( P < 0.01), increasing awareness about deceased organ donation ( P < 0.01), and advertising for transplant centers ( P < 0.01). Individual characteristics influence opinions about the role and clinical usefulness of social media. Conclusions: Transplant center involvement and support for social media may influence clinician perceptions and practices. Increasing use of social media among transplant professionals may provide an opportunity to deliver high-quality information to patients. Abstract : Supplemental Digital Content is available in the text.